Carbonic anhydrase inhibition blocks skeletogenesis and echinochrome production in Paracentrotus lividus and Heliocidaris tuberculata embryos and larvae. (23rd June 2015) - Zito, Francesca; Koop, Demian; Byrne, Maria; Matranga, Valeria
<x xml:space="preserve">Abstract</x> Carbonic anhydrases (CAs) are a family of widely distributed metalloenzymes, involved in diverse physiological processes. These enzymes catalyse the reversible conversion of carbon dioxide to protons and bicarbonate. At least 19 genes encoding for CAs have been identified in the sea urchin genome, with one of these localized to the skeletogenic mesoderm (primary mesenchyme cells, PMCs). We investigated the effects of a specific inhibitor of CA, acetazolamide (AZ), on development of two sea urchin species with contrasting investment in skeleton production, Paracentrotus lividus and Heliocidaris tuberculata, to determine the role of CA on PMC differentiation, skeletogenesis and on non‐skeletogenic mesodermal (NSM) cells. Embryos were cultured in the presence of AZ from the blastula stage prior to skeleton formation and development to the larval stage was monitored. At the dose of 8 mmol/L AZ, 98% and 90% of P. lividus and H. tuberculata embryos lacked skeleton, respectively. Nevertheless, an almost normal PMC differentiation was indicated by the expression of msp130, a PMC‐specific marker. Strikingly, the AZ‐treated embryos also lacked the echinochrome pigment produced by the pigment cells, a subpopulation of NSM cells with immune activities within the larva. Conversely, all ectoderm and endoderm derivatives and other subpopulations of mesoderm developed normally. The inhibitory effects of AZ were completely reversed after removal of the inhibitor from the medium. Our data, together with new information concerning the involvement of CA on skeleton formation, provide evidence for the first time of a possible role of the CAs in larval immune pigment cells.